Validation of the Arabic version of the Epworth Sleepiness Scale - Anwar E. Ahmed; Abdulhamid Fatani; Abdullah Al-Harbi; Abdullah Al-Shimemeri; Yosra Z. Ali; Salim Baharoon; Hamdan Al-Jahdali (Springer, 2019)
Background: The Epworth Sleepiness Scale (ESS) is a questionnaire widely used in developed countries to measure daytime sleepiness and diagnose sleep disorders. Objective: This study aimed to develop an ESS questionnaire for the Arabic population (ArESS), to determine ArESS internal consistency, and to measure ArESS test-retest reproducibility. It also investigated whether the normal range of ESS scores of healthy people in different cultures are similar. Methods: The original ESS questionnaire was translated from English to Arabic and back-translated to English. In both the English and Arabic translations of the survey, ESS consists of eight different situations. The subject was asked to rate the chance of dozing in each situation on a scale of 0-3 with total scores ranging between 0 (normal sleep) and 24 (very sleepy). An Arabic translation of the ESS questionnaire was administered to 90 healthy subjects. Results: Item analysis revealed high internal consistency within ArESS questionnaire (Cronbach's alpha = 0.86 in the initial test, and 0.89 in the retest). The test-retest intra-class correlation coefficient (ICC) shows that the test-retest reliability was substantially high: ICC = 0.86 (95% confidence interval: 0.789-0.909, p-value < 0.001). The difference in ArESS scores between the initial test and retest was not significantly different from zero (average difference = −0.19, t = −0.51, df = 89, p-value = 0.611). In this study, the averages of the ESS scores (6.3 ± 4.7, range 0-20 in the initial test and 6.5 ± 5.3, range 0-20 in the retest) are considered high in Western cultures. Conclusions: The study shows that the ArESS is a valid and reliable tool that can be used in Arabic-speaking populations to measure daytime sleepiness. The current study has shown that the average ESS score of healthy Arabian subjects is significantly higher than in Western cultures.